Pivotal role of solid phase interactions in the pressure-induced bi-stability of cyanide-bridged Fe2Co2 square complexes - Xu, Buqin; Li, Yanling; Gontard, Geoffrey; Béneut, Keevin; Parisiades, Paraskevas; Deutsch, Maxime; Rodrigue Lescouëzec (Inorganic chemistry frontiers, 2025)
Cyanide-bridged FeCo coordination clusters, recognized as exceptional candidates for molecular switches, have been the subject of extensive research efforts aimed at unraveling the key factors governing the charge transfer process. Previously, we have observed that the square complex {[Fe(Tp)(CN)3]2[Co(vbik)2]2}2+ with Tp = tris(pyrazolyl)borate and vbik = bis(1-vinyl-2-imidazolyl)ketone, abbreviated as Fe2Co2, undergoes thermal charge transfer in MeOH solution near room temperature allowing the obtention of a solvatomorph pair, Fe2IIICo2II·2BF4·2MeOH (1) and Fe2IICo2III·2BF4·10H2O·2MeOH (2), exhibiting distinct electronic configurations at 300 K. While 2 maintains its charge transfer ability in the solid state, 1 is trapped in the paramagnetic state by solid phase interactions down to 2 K, which makes it a good candidate for investigating electron transfer under hydrostatic pressure, an external stimulus scarcely used for these systems. In the present work, we demonstrated that the synthesis method can be used to obtain a new solvatomorph with remarkable pressure-induced electron transfer. The paramagnetic Fe2IIICo2II·2(PF6)·2MeOH (3) and the diamagnetic Fe2IICo2III·2(PF6)·nH2O·mMeOH (4), isostructural to 1 and 2, respectively, were obtained. The stronger intermolecular interactions due to the PF6 anion lead to a greater distortion of the core structures of 3 and 4, affecting their magnetic properties under ambient and hydrostatic pressure. Notably, 3 exhibits a partial pressure-induced conversion from a paramagnetic to a diamagnetic state followed by a back conversion above a pressure threshold value, which is rationalized by a symmetry-breaking phase transition at ca. 0.96–1.0 GPa. This unusual behavior has been analyzed using magnetometry, X-ray diffraction, and μ-Raman spectroscopy under various pressures. A deeper understanding of the electron transfer process in 3 was achieved by analyzing its structural data under various pressures and comparing them to those of 1. The distinct electron transfer behaviors observed in the two complexes are likely correlated to the differing distortions in their square core structures induced by pressure.